Fatal antral ulcer in conventionally fed W/Wv mutant mice given indomethacin by injection. - Yokoyama, M. (1985)
Antral ulcers develop spontaneously in (WB X C57BL/6)F1-W/Wv mice. Most W/Wv mice with severe ulcers die within 3 months after birth. When healthy-looking W/Wv mice were selected at 4 months of age, 80-90% of them were free from the ulcer. Even if the ulcer was present, it was small. The authors compared the susceptibility of such healthy-looking W/Wv mice to ulcerogenic treatments with that of the congenic +/+ mice. Stress caused development of fundic erosions in both W/Wv and +/+ mice. The susceptibility of the W/Wv mice to either cold or water-immersed stress was not higher than that of the +/+ mice. Topical administration of aspirin produced erosions in both fundus and antrum. The susceptibility of W/Wv mice to aspirin was comparable to that of the +/+ mice in either the starved or the fed condition. Subcutaneous injection of indomethacin produced both fundic erosions and antral ulcers in the starved condition, but it produced only antral ulcers in the conventionally fed condition. The susceptibility of the starved W/Wv mice to indomethacin was not higher than that of the starved +/+ mice. In contrast, the fed W/Wv mice were significantly more susceptible to indomethacin than the fed +/+ mice. A considerable proportion of the fed W/Wv mice died of blood loss from the ulcer within 24 hours. The size of the ulcer of the W/Wv mice was significantly larger than that of the +/+ mice. Both genetic and feeding conditions seem to determine the susceptibility to indomethacin.